Relationship between anthropometric and motor characteristics and swimming performance over 400 meters freestyle in young swimmers - Esin Çağla Çağlar; Turgut Yildirim; Mehmet Kutlu; Furkan Çamiçi; Tuğrul Özkaldı (ROL Spor Bilimleri Dergisi)
This study analyzes the effects of anthropometric and motor characteristics on the swimming performance of male swimmers aged 12-15 years. The aim of the study was to measure participants’ shoulder width, grip strength, flexibility and aerobic endurance and to investigate the correlation of these data with swimming times over 400 meters freestyle. The study focuses on two age groups (12-13 and 14-15) and identifies the factors that influence performance in the different age groups. The anthropometric and motor characteristics of the participants were measured using a Tanita BC 418 bioelectrical impedance device and the data obtained were analyzed by a simple linear regression analysis. The results showed that shoulder width, hand grip strength, flexibility and aerobic endurance significantly affected performance in the 12-13 age group (p<0.05), while body weight, upper body length, muscle strength, flexibility and aerobic endurance more significantly affected performance in the 14-15 age group (p<0.05). The results of the study highlight that the characteristics that influence young swimmers’ performance differ between age groups and therefore require group-specific and personalized training programs. These results provide important information for coaches and sports scientists to improve swimming performance.